Velvet goldmine die total schräge 70er Party - McGregor, Ewan 1971-; Rhys-Meyers, Jonathan 1977-; Collette, Toni 1972-; Bale, Christian 1974-; Haynes, Todd 1961-; Izzard, Eddie 1962-; Woof, Emily 1967-; Feast, Michael; Lyons, James K. 1960-2007 (Universum Film, 2010)
In 1984, British journalist Arthur Stuart investigates the career of 1970s glam superstar Brian Slade, who was heavily influenced in his early years by hard-living and rebellious American singer Curt Wild. [IMDb]
Bild: 1,85:1 (16:9 anamorph)
Special features: Deutsches Making of; Englisches Making of; Videoclip "Baby's on fire"
Orig.: Großbritannien/USA, 1998
Keywords: Musical films; Musikfilm; Film; DVD-Video